(untitled) (Ecological Bulletin of Kryvyi Rih District, 2019)
Repressing and eliminate inﬂuence of 35% bischoﬁte solutionis revealed on the reproductive sphere of Аmbrosia artemisiifolia. Abnormal and sterile antheriferous grains increased because of Аmbrosia artemisiifolia’s sprinkling with bischoﬁte solution